Effects of prohydrojasmon‐treated corn plants on attractiveness to parasitoids and the performance of their hosts. (18th April 2012) - Mandour, N. S.; Kainoh, Y.; Ozawa, R.; Uefune, M.; Takabayashi, J.
Abstract We investigated the effect of prohydrojasmon [propyl (1RS, 2RS)‐(3‐oxo‐ 2‐pentylcyclopentyl) acetate] (PDJ) treatment of intact corn plants, on their attractiveness to the specialist endoparasitoid, Cotesia kariyai Watanabe (Hymenoptera: Braconidae), and on the performance of the common armyworm, Mythimna separata (Walker) (Lepidoptera: Noctuidae) under laboratory conditions. Attractiveness of C. kariyai to PDJ‐treated plants was studied in a wind tunnel, whereas performance of M. separata larvae was tested in plastic cages. The attractiveness of the treated plants increased with concentrations of PDJ increasing to 2 mm, which was equivalent to the attractiveness of host‐infested plants. PDJ‐treated corn plants emitted 16 volatile compounds (α‐pinene, β‐myrcene, (Z)‐3‐hexenyl acetate, limonene, (E)‐β‐ocimene, linalool, (E)‐4, 8‐dimethyl‐1, 3, 7‐nonatriene, (+)‐cyclosativene, ylangene, (E)‐β‐farnesene, (E, E)‐4, 8, 12‐trimethyl‐1, 3, 7, 11‐tridecatetraene, α‐bergamotene, γ‐cadinene, δ‐cadinene, α‐muulolene and nerolidol), most of which were observed in the headspace of host‐infested corn plants with some quantitative and qualitative differences. We also tested the effects of PDJ treatment on the performance of M. separata larvae. The survival rates of the larval and pupal stages were significantly lower at 2 mm level of PDJ. A significant decrease in weight at 6th stadium larvae was observed only at 2 mm level of PDJ. In contrast, PDJ treatment at all PDJ concentration levels caused significant reduction in weight of pupal stage as compared to control. These data suggested that PDJ, originally developed as a plant growth regulator, especially to induce coloring of fruits, has the potential to induce direct and indirect defenses in corn plants against common armyworm, M. separata.